CrAlN / TiAlN multilayer cutter coating capable of remarkably prolonging service life of end mill and preparation method of CrAlN / TiAlN multilayer cutter coating
The preparation of CrAlN/TiAlN multi-layer tool coating through multi-arc ion coating technology solves the problems of short service life of existing tools and limited bearing capacity of single-layer nitride coatings, and achieves the effect of significantly improving tool hardness and service life.
Patent Information
- Application Number
- CN202411971861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
Existing tools have short service life in machining, and single-layer nitride coatings have limited load-bearing and crack-propagation resistance.
Multi-arc ion coating technology is used to prepare CrAlN/TiAlN multi-layer tool coating, which consists of a CrN/Cr transition layer and alternately deposited CrAlN and TiAlN layers, and the hardness and binding force of the coating are improved through multi-layer structure regulation.
It significantly improves the service life of the end mill, improves the hardness and wear resistance of the tool, and optimizes the tribological performance and extends the processing efficiency and life of the tool.
Smart Images

Figure CN119843217A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of PVD hard coating material protection, and in particular to a CrAlN / TiAlN multilayer tool coating which can significantly improve the service life of an end mill and has high hardness and high wear resistance, and a preparation method thereof. Background Art
[0002] Modern metal cutting is developing towards high speed, high precision and high efficiency, and has higher and higher requirements for tool performance. Practice has shown that it is not only technically difficult to improve tool performance from the perspective of tool structure design, manufacturing process or materials, but also extremely uneconomical in terms of resource utilization. Using surface technology to modify the tool surface is an effective way to improve tool processing efficiency and life, and has the advantages of economy and high efficiency, so it is widely used.
[0003] Transition metal nitride coatings have better mechanical properties, wear resistance and thermal stability than pure metal coatings, and are widely used in cutting tools, molds, automotive parts, aerospace and other fields.
[0004] Although the single-layer nitride coating has excellent tribological properties, its load-bearing and crack-resistance capabilities are limited, so its use is limited. Nano-multilayer structure regulation refers to the alternating deposition of two or more coating materials on the substrate material, which is a common method for toughening transition metal nitride coatings.
[0005] The metastable MeAlN coating, which is formed by Al replacing part of the Me in the cubic structure (c) transition metal nitride MeN (Me = Ti, Zr, Cr, etc.), has become a research hotspot for tool coatings due to its excellent properties such as high hardness, high melting point and good oxidation resistance.
[0006] In summary, the present invention is proposed in combination with the advantages of surface coating technology in improving tool performance and the advantages of the structure and material properties of the CrAlN / TiAlN multilayer coating. Summary of the invention
[0007] In view of the problems existing in current mechanical processing, the present invention provides a CrAlN / TiAlN multilayer tool coating and a preparation method thereof that can significantly improve the service life of an end mill. The CrAlN / TiAlN multilayer tool coating has excellent bonding strength and high hardness while exhibiting excellent tribological properties. The coating can be well deposited on the surface of the tool and applied to mechanical processing to improve the service life and performance of the tool.
[0008] The above-mentioned purpose of this article is achieved through the following technical methods.
[0009] The present invention provides a CrAlN / TiAlN multilayer tool coating that can significantly improve the service life of an end mill. The CrAlN / TiAlN multilayer tool coating is prepared using a multi-arc ion plating technology and consists of a CrN / Cr transition layer and a CrAlN / TiAlN multilayer coating; the CrAlN / TiAlN multilayer tool coating is prepared using a multi-arc ion plating technology to first deposit a CrN / Cr transition layer on a polished and cleaned substrate surface, and then alternately deposit a TiAlN layer and a CrAlN layer on the transition layer, wherein a TiAlN layer is deposited on the surface of the transition layer, and the outermost layer is a CrAlN layer.
[0010] Preferably, the total thickness of the CrAlN / TiAlN multilayer tool coating is 2.6μm to 3.2μm, the thickness of the CrN / Cr transition layer is about 500nm, the thickness of each CrAlN coating layer is 250nm to 1.1μm, the thickness of each TiAlN coating layer is 260nm to 1.3μm, and the total number of periodic layers is 2 to 10 layers.
[0011] Preferably, the CrAlN layer and the TiAlN layer are (Cr, Al)N and (Ti, Al)N solid solution phases, respectively.
[0012] The present invention also provides a method for preparing a CrAlN / TiAlN multilayer tool coating. The coating preparation method is simple, the deposition structure is highly adjustable, and the single-layer thickness is precisely controlled. The multi-arc ion plating technology has the advantages of fast deposition speed and strong adhesion of the deposited coating, thereby shortening the preparation time while ensuring the film-base adhesion of the coating.
[0013] The present invention adopts a multi-arc ion plating device, which mainly comprises a vacuum chamber, a first arc source, a second arc source, a third arc source, a bias power supply, a heating unit, a rotating unit, an air intake unit and a vacuum acquisition system. The first arc source, the second arc source, the third arc source and the ion source are evenly distributed on the inner wall of the vacuum chamber, and a rotating frame that can rotate is arranged in the center of the vacuum chamber, and the rotating frame has a revolution rod and a rotation rod.
[0014] Furthermore, in the present invention, the first arc source is connected to a Cr target, the second arc source is mounted on a TiAl target, the third arc source is mounted on a CrAl target, the substrate is mounted on a revolving rod of a rotating frame, and the tool is mounted on a rotating rod of the rotating frame.
[0015] The preparation method of the CrAlN / TiAlN multilayer tool coating that significantly improves the service life of the end mill specifically comprises the following steps:
[0016] (1) Pre-treatment:
[0017] Use a polishing machine to grind and polish the sample surface to a mirror surface, place the polished sample and tool in acetone and anhydrous ethanol for ultrasonic cleaning to remove surface stains, and place the cleaned sample and tool in an oven at 70-80°C for heat preservation;
[0018] (2) Substrate etching
[0019] The substrate and tool processed in step (1) are fixed on the rotating rack in the furnace by a fixture, and the rotating rack speed is set to 1-1.5 r / min; the vacuum degree of the chamber is higher than 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber is higher than 5×10 -3 When the temperature in the furnace reaches 330-400°C, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1-1.5 Pa, the bias power supply is turned on to adjust the negative bias voltage to increase linearly from -400 V to -800 V. The ion source power is 0.7-1.5 kW and argon ion etching is performed for 10-30 min.
[0020] (3) Deposition of CrN / Cr transition layer
[0021] After the etching in step (2) is completed, the ion source is turned off, the baffle is moved to block the target material, and the target material is ignited for 1 to 2 minutes to clean the surface of the target material to remove oxides and contaminants on the surface of the target material; the baffle is removed, a nitrogen flow rate of 30 to 100 sccm and an argon flow rate of 80 to 150 sccm are introduced, the throttle valve is controlled to maintain the pressure in the chamber at 1 to 1.5 Pa, the bias voltage is adjusted to -40 V and the Cr target power supply is turned on; the target current is set to 60 to 100 A to prepare the transition layer, and the deposition time is 15 to 30 minutes. During this period, the gas flow rate and the substrate bias voltage are set to change linearly, the nitrogen flow rate is linearly increased to 600 to 700 sccm, the argon flow rate is linearly reduced to 0, the substrate bias voltage is linearly increased to -80 V and the vacuum degree is always maintained at 1 to 1.5 Pa, and a CrN / Cr transition layer is obtained;
[0022] (4) Alternating deposition of CrAlN / TiAlN coatings
[0023] Step (3) After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600-650sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias voltage is adjusted to -60V; first, the TiAl target power supply is turned on, the arc current is set to 60-100A, and the deposition is carried out for 9min-45min, during which the arc current increases linearly from 60-80A to 80-100A, and the substrate bias voltage increases to -100V; after the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias voltage is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 60-100A, and the deposition is carried out for 9min-45min, during which the arc current increases linearly from 60-80A to 80-100A, and the substrate bias voltage increases to -100V; the deposition is repeated several times in this way, and the total deposition time is 70-100min; finally, a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface is obtained.
[0024] Preferably, the substrate selected in step (1) can be made of metal, ceramic or other materials.
[0025] Preferably, in step (1), the ultrasonic cleaning time is 10 to 15 minutes; and the insulation time is 15 to 20 minutes.
[0026] Preferably, the purity of the Cr target used in step (3) is 99.99%.
[0027] Preferably, the CrAl target in step (4) is composed of two elements, Cr and Al, wherein the atomic ratio of Cr:Al is 3:7 to 3.33:6.66, preferably 3:7, and the purity is 99.99%.
[0028] Preferably, the TiAl target in step (4) is composed of two elements, Ti and Al, wherein the atomic ratio of Ti:Al is 3:7 to 3.33:6.66, preferably 3:7, and the purity is 99.99%.
[0029] Preferably, the rotation speed of the rotating rack during the preparation process of steps (1), (2), (3) and (4) is 1 to 1.5 rpm, preferably 1 rpm.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) The CrN / Cr transition layer designed by the present invention can significantly improve the bonding strength between the coating and the substrate while effectively preventing the diffusion of substrate elements into the CrAlN / TiAlN multilayer coating, which is beneficial to maintaining the purity and performance of the coating. The transition structure from Cr to CrN can reduce the stress between the substrate and the transition layer while ensuring the hardness of the transition layer.
[0032] (2) The multilayer structure of the multilayer coating can effectively regulate the stress distribution within the coating and optimize the stress accumulation during the coating deposition process, thereby achieving a toughening effect.
[0033] (3) The grains of the CrAlN / TiAlN multilayer coating are fine, and the CrAlN layer and the TiAlN layer are (Cr, Al)N and (Ti, Al)N solid solution phases, respectively.
[0034] (4) CrAlN / TiAlN multilayer coating can simultaneously possess the high-temperature mechanical properties of TiAlN and the high-temperature stability of CrAlN, achieving the effect of strengthening and protecting the substrate.
[0035] (5) The CrAlN / TiAlN multilayer coating of the present invention adopts multi-arc ion plating technology, which has the characteristics of fast coating deposition speed and strong adhesion of the deposited coating, thereby shortening the preparation time while ensuring the film-base adhesion of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a cross-sectional scanning electron microscope photograph of the CrAlN / TiAlN multilayer coating obtained in Example 1;
[0037] Figure 2a and Figure 2b They are optical microscopic images comparing the wear scar morphologies of the CrAlN / TiAlN multilayer coating obtained in Example 1 and the substrate at room temperature;
[0038] Figure 3a and Figure 3b They are respectively optical microscopic images of the wear morphology of the first bottom edge flank surface obtained after the three-edge cemented carbide end mill with CrAlN / TiAlN multilayer coating and the three-edge cemented carbide end mill without coating obtained in Example 1 milled the same volume of 45 steel under the same working conditions;
[0039] Figure 4 This is a ball milling treatment image of the surface of the CrAlN / TiAlN multilayer coating obtained in Example 5;
[0040] Figure 5 This is a photo of the CrAlN / TiAlN multilayer coating tool obtained in Example 5. Specific implementation methods
[0042] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the specific implementation method of the present invention is not limited thereto.
[0043] Example 1
[0044] The specific preparation method of the CrAlN / TiAlN multilayer coating of this embodiment that significantly improves the service life of the end mill is as follows:
[0045] The polished sample and tool were placed in acetone and anhydrous ethanol for ultrasonic cleaning for 10 minutes to remove surface stains. The cleaned sample and tool were placed in an oven and kept warm at 80°C for 20 minutes. The treated substrate and tool were fixed on the rotating rack in the furnace by a clamp, and the rotating rack speed was set to 1r / min. The vacuum degree of the cavity reached 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber reaches 5×10 -3 Pa and the temperature in the furnace reaches 350℃, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1Pa, the bias power supply is turned on to adjust the negative bias voltage from -400V to -800V linearly. The ion source power is 1.0kW for argon ion etching for 15min. After the etching is completed, the ion source is turned off, the baffle is moved to block the target, and the target is ignited for 1min to clean the target surface to remove oxides and contaminants on the target surface. The baffle is removed and the nitrogen flow rate is 30sccm and the argon flow rate is 100sccm. After the throttle valve is controlled to maintain the gas pressure in the chamber at 1Pa, the bias voltage is adjusted to -40V and the Cr target power supply is turned on. The target current is set to 80A to prepare the transition layer. The deposition time is 15min. During this period, the gas flow rate and substrate bias voltage are set to change linearly. The nitrogen flow rate increases linearly to 600sccm, the argon flow rate decreases linearly to 0, and the substrate bias voltage increases linearly to -80V while the vacuum degree is always maintained at 1Pa. After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias is adjusted to -60V. First, the TiAl target power supply is turned on, the arc current is set to 80A, and the deposition is 45min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. After the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 80A, and the deposition is 45min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. This alternating deposition is performed once. After the preparation is completed, it is cooled naturally to finally obtain a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface.
[0046] The CrAlN / TiAlN multilayer coating obtained in this embodiment has a total thickness of 2.9 μm, a single layer thickness of CrAlN of 1.1 μm, and a thickness of each TiAlN layer of 1.3 μm. The microhardness and bonding strength of the coating are 2651 HV and 59.2 N, respectively. Figure 1The cross-sectional morphology of the CrAlN / TiAlN multilayer coating obtained in this example is shown in the electron microscope image, where the gray layer in contact with the substrate is the CrN / Cr transition layer, the black layer deposited on the transition layer is the TiAlN layer, and the top layer is the CrAlN layer. Under the same friction test conditions, the optical microscope images of the wear scar morphology of the coating sample obtained in this example and the substrate are shown in Figure 2. Figure 2a and Figure 2b The optical microscopic images of the wear morphology of the first bottom edge flank surface obtained after the three-edge cemented carbide end mill with the CrAlN / TiAlN multilayer coating of Example 1 deposited on the surface and the uncoated three-edge cemented carbide end mill milled the same volume of 45 steel under the same working conditions are shown in Figure 1. Figure 3a and Figure 3b shown.
[0047] Example 2
[0048] The specific preparation method of the CrAlN / TiAlN multilayer coating of this embodiment that significantly improves the service life of the end mill is as follows:
[0049] The polished sample and tool were placed in acetone and anhydrous ethanol for ultrasonic cleaning for 10 minutes to remove surface stains. The cleaned sample and tool were placed in an oven and kept warm at 80°C for 20 minutes. The treated substrate and tool were fixed on the rotating rack in the furnace by a clamp, and the rotating rack speed was set to 1r / min. The vacuum degree of the cavity reached 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber reaches 5×10 -3Pa and the temperature in the furnace reaches 350℃, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1Pa, the bias power supply is turned on to adjust the negative bias voltage from -400V to -800V linearly. The ion source power is 1.0kW for argon ion etching for 15min. After the etching is completed, the ion source is turned off, the baffle is moved to block the target, and the target is ignited for 1min to clean the target surface to remove oxides and contaminants on the target surface. The baffle is removed and the nitrogen flow rate is 30sccm and the argon flow rate is 100sccm. After the throttle valve is controlled to maintain the gas pressure in the chamber at 1Pa, the bias voltage is adjusted to -40V and the Cr target power supply is turned on. The target current is set to 80A to prepare the transition layer. The deposition time is 15min. During this period, the gas flow rate and substrate bias voltage are set to change linearly. The nitrogen flow rate increases linearly to 600sccm, the argon flow rate decreases linearly to 0, and the substrate bias voltage increases linearly to -80V while the vacuum degree is always maintained at 1Pa. After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias is adjusted to -60V. First, the TiAl target power supply is turned on, the arc current is set to 80A, and the deposition is 15min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. After the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 80A, and the deposition is 15min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. This is alternately deposited 3 times. After the preparation is completed, it is cooled naturally, and finally a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface is obtained.
[0050] The CrAlN / TiAlN multilayer coating prepared in this embodiment was tested to have a total thickness of 3.1 μm, a single layer thickness of CrAlN of 400 nm, and a thickness of each TiAlN layer of 410 nm. The microhardness and bonding strength of the coating were 2792 HV and 53.5 N, respectively.
[0051] Example 3
[0052] The specific preparation method of the CrAlN / TiAlN multilayer coating of this embodiment that significantly improves the service life of the end mill is as follows:
[0053] The polished sample and tool were placed in acetone and anhydrous ethanol for ultrasonic cleaning for 10 minutes to remove surface stains. The cleaned sample and tool were placed in an oven and kept warm at 80°C for 20 minutes. The treated substrate and tool were fixed on the rotating rack in the furnace by a clamp, and the rotating rack speed was set to 1r / min. The vacuum degree of the cavity reached 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber reaches 5×10 -3Pa and the temperature in the furnace reaches 350℃, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1Pa, the bias power supply is turned on to adjust the negative bias voltage from -400V to -800V linearly. The ion source power is 1.0kW for argon ion etching for 15min. After the etching is completed, the ion source is turned off, the baffle is moved to block the target, and the target is ignited for 1min to clean the target surface to remove oxides and contaminants on the target surface. The baffle is removed and the nitrogen flow rate is 30sccm and the argon flow rate is 100sccm. After the throttle valve is controlled to maintain the gas pressure in the chamber at 1Pa, the bias voltage is adjusted to -40V and the Cr target power supply is turned on. The target current is set to 80A to prepare the transition layer. The deposition time is 15min. During this period, the gas flow rate and substrate bias voltage are set to change linearly. The nitrogen flow rate increases linearly to 600sccm, the argon flow rate decreases linearly to 0, and the substrate bias voltage increases linearly to -80V while the vacuum degree is always maintained at 1Pa. After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias is adjusted to -60V. First, the TiAl target power supply is turned on, the arc current is set to 80A, and the deposition is 12min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. After the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 80A, and the deposition is 12min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. This is alternately deposited 4 times. After the preparation is completed, it is cooled naturally, and finally a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface is obtained.
[0054] The CrAlN / TiAlN multilayer coating prepared in this embodiment was tested to have a total thickness of 3.2 μm, a single layer thickness of CrAlN of 320 nm, and a thickness of each TiAlN layer of 340 nm. The microhardness and bonding strength of the coating were 2317 HV and 48.6 N, respectively.
[0055] Example 4
[0056] The specific preparation method of the CrAlN / TiAlN multilayer coating of this embodiment that significantly improves the service life of the end mill is as follows:
[0057] The polished sample and tool were placed in acetone and anhydrous ethanol for ultrasonic cleaning for 10 minutes to remove surface stains. The cleaned sample and tool were placed in an oven and kept warm at 80°C for 20 minutes. The treated substrate and tool were fixed on the rotating rack in the furnace by a clamp, and the rotating rack speed was set to 1r / min. The vacuum degree of the cavity reached 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber reaches 5×10 -3Pa and the temperature in the furnace reaches 350℃, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1Pa, the bias power supply is turned on to adjust the negative bias voltage from -400V to -800V linearly. The ion source power is 1.0kW for argon ion etching for 15min. After the etching is completed, the ion source is turned off, the baffle is moved to block the target, and the target is ignited for 1min to clean the target surface to remove oxides and contaminants on the target surface. The baffle is removed and the nitrogen flow rate is 30sccm and the argon flow rate is 100sccm. After the throttle valve is controlled to maintain the gas pressure in the chamber at 1Pa, the bias voltage is adjusted to -40V and the Cr target power supply is turned on. The target current is set to 80A to prepare the transition layer. The deposition time is 15min. During this period, the gas flow rate and substrate bias voltage are set to change linearly. The nitrogen flow rate increases linearly to 600sccm, the argon flow rate decreases linearly to 0, and the substrate bias voltage increases linearly to -80V while the vacuum degree is always maintained at 1Pa. After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias is adjusted to -60V. First, the TiAl target power supply is turned on, the arc current is set to 80A, and the deposition is 9min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. After the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 80A, and the deposition is 9min. During this period, the arc current increases linearly from 80A to 100A, and the substrate bias increases to -100V. This is alternately deposited 5 times. After the preparation is completed, it is cooled naturally to finally obtain a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface.
[0058] The CrAlN / TiAlN multilayer coating prepared in this embodiment is tested to have a total thickness of 2.9 μm, a single layer thickness of CrAlN of 230 nm, and a thickness of each layer of TiAlN of 250 nm. The microhardness and bonding strength of the coating are 2123 HV and 42.5 N, respectively. Figure 5 shown.
Claims
1. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill, characterized in that: The CrAlN / TiAlN multilayer tool coating is prepared by multi-arc ion plating technology, and is composed of a CrN / Cr transition layer and a CrAlN / TiAlN multilayer coating; the CrAlN / TiAlN multilayer tool coating is prepared by multi-arc ion plating technology, firstly depositing a CrN / Cr transition layer on the surface of a polished and cleaned substrate, and then alternately depositing a TiAlN layer and a CrAlN layer on the transition layer, wherein a TiAlN layer is deposited on the surface of the transition layer, and the outermost layer is a CrAlN layer; The steps include: (1) Pre-treatment: Use a polishing machine to grind and polish the sample surface to a mirror surface, place the polished sample and tool in acetone and anhydrous ethanol for ultrasonic cleaning to remove surface stains, and place the cleaned sample and tool in an oven at 70-80°C for heat preservation; (2) Substrate etching The substrate and tool processed in step (1) are fixed on the rotating rack in the furnace by a fixture, and the rotating rack speed is set to 1-1.5 r / min; the vacuum degree of the chamber is higher than 7×10 -2 Pa, heating begins, and the vacuum degree of the chamber is higher than 5×10 -3 When the temperature in the furnace reaches 330-400°C, argon gas is introduced into the chamber. When the gas pressure stabilizes at 1-1.5 Pa, the bias power supply is turned on to adjust the negative bias voltage to increase linearly from -400 V to -800 V. The ion source power is 0.7-1.5 kW and argon ion etching is performed for 10-30 min. (3) Deposition of CrN / Cr transition layer After the etching in step (2) is completed, the ion source is turned off, the baffle is moved to block the target material, and the target material is ignited for 1 to 2 minutes to clean the surface of the target material to remove oxides and contaminants on the surface of the target material; the baffle is removed, a nitrogen flow rate of 30 to 100 sccm and an argon flow rate of 80 to 150 sccm are introduced, the throttle valve is controlled to maintain the pressure in the chamber at 1 to 1.5 Pa, the bias voltage is adjusted to -40 V and the Cr target power supply is turned on; the target current is set to 60 to 100 A to prepare the transition layer, and the deposition time is 15 to 30 minutes. During this period, the gas flow rate and the substrate bias voltage are set to change linearly, the nitrogen flow rate is linearly increased to 600 to 700 sccm, the argon flow rate is linearly reduced to 0, the substrate bias voltage is linearly increased to -80 V and the vacuum degree is always maintained at 1 to 1.5 Pa, and a CrN / Cr transition layer is obtained; (4) Alternating deposition of CrAlN / TiAlN coatings Step (3) After the transition layer is prepared, the Cr target power supply is turned off, the nitrogen flow rate is set to 600-650sccm, and the vacuum degree in the chamber is maintained at 2Pa by adjusting the throttle valve, and then the substrate bias voltage is adjusted to -60V; first, the TiAl target power supply is turned on, the arc current is set to 60-100A, and the deposition is carried out for 9min-45min, during which the arc current increases linearly from 60-80A to 80-100A, and the substrate bias voltage increases to -100V; after the TiAlN layer is deposited, the TiAl target power supply is turned off, the substrate bias voltage is adjusted to -60V, and the CrAl target power supply is turned on, the arc current is set to 60-100A, and the deposition is carried out for 9min-45min, during which the arc current increases linearly from 60-80A to 80-100A, and the substrate bias voltage increases to -100V; the deposition is repeated several times in this way, and the total deposition time is 70-100min; finally, a CrAlN / TiAlN multilayer coating deposited on the substrate and the tool surface is obtained.
2. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: In step (1), the selected sample is metal, ceramic or cemented carbide.
3. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: In step (1), the ultrasonic cleaning time is 10 to 15 minutes; the insulation time is 15 to 20 minutes.
4. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: The purity of the Cr target used in step (3) is 99.99%.
5. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: The CrAl target in step (4) is composed of two elements, Cr and Al, wherein the atomic ratio of Cr:Al is 3:7 to 3.33:6.66, and the purity is 99.99%.
6. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: The TiAl target in step (4) is composed of two elements, Ti and Al, wherein the atomic ratio of Ti:Al is 3:7 to 3.33:6.66, and the purity is 99.99%.
7. A method for preparing a CrAlN / TiAlN multilayer tool coating that significantly improves the service life of an end mill as claimed in claim 1, characterized in that: During the preparation process of steps (1), (2), (3) and (4), the rotation speed of the rotating rack is 1 to 1.5 rpm.
8. A CrAlN / TiAlN multilayer tool coating prepared by the preparation method according to any one of claims 1 to 7.
9. The CrAlN / TiAlN multilayer tool coating according to claim 8, characterized in that: The total thickness of the CrAlN / TiAlN multilayer tool coating is 2.6μm-3.2μm, the thickness of the CrN / Cr transition layer is about 550-600nm, the thickness of each CrAlN coating layer is 250nm-1.1μm, the thickness of each TiAlN coating layer is 260nm-1.3μm, and the total number of periodic layers is 2-10 layers.
10. The CrAlN / TiAlN multilayer tool coating according to claim 7, characterized in that: The CrAlN layer and the TiAlN layer are (Cr, Al)N and (Ti, Al)N solid solution phases respectively.
Citation Information
Cited By
Cutter coating as well as cutting tool and preparation method thereof
CN120844014A